SOLUBILITY PRODUCTS OF AMORPHOUS FERRIC ARSENATE AND CRYSTALLINE SCORODITE (FEASO4·2H2O) AND THEIR APPLICATION TO ARSENIC BEHAVIOR IN BURIED MINE TAILINGS - Langmuir D.; Mahoney J.; Rowson J. (My University, 2006)
Published solubility data for amorphous ferric arsenate and scorodite have been reevaluated using the geochemical code PHREEQC with a modified thermodynamic database for the arsenic species. Solubility product calculations have emphasized measurements obtained under conditions of congruent dissolution of ferric arsenate (pH < 3), and have taken into account ion activity coefficients, and ferric hydroxide, ferric sulfate, and ferric arsenate complexes which have association constants of 104.04 (FeH2AsO42+), 109.86 (FeHAsO4+), and 1018.9 (FeAsO4). Derived solubility products of amorphous ferric arsenate and crystalline scorodite (as log Ksp) are -23.0 ? 0.3 and -25.83 ? 0.07, respectively, at 25 °C and 1 bar pressure. In an application of the solubility results, acid raffinate solutions (molar Fe/As = 3.6) from the JEB uranium mill at McClean Lake in northern Saskatchewan were neutralized with lime to pH 2-8. Poorly crystalline scorodite precipitated below pH 3, removing perhaps 98% of the As(V) from solution, with ferric oxyhydroxide (FO) phases precipitated starting between pH 2 and 3. Between pH 2.18 and 7.37, the apparent log Ksp of ferric arsenate decreased from -22.80 to -24.67, while that of FO (as Fe(OH)3) increased from -39.49 to -33.5. Adsorption of As(V) by FO can also explain the decrease in the small amounts of As(V)(aq) that remain in solution above pH 2-3. The same general As(V) behavior is observed in the pore waters of neutralized tailings buried for 5 yr at depths of up to 32 m in the JEB tailings management facility (TMF), where arsenic in the pore water decreases to 1-2 mg/L with increasing age and depth. In the TMF, average apparent log Ksp values for ferric arsenate and ferric hydroxide are -25.74 ? 0.88 and -37.03 ? 0.58, respectively. In the laboratory tests and in the TMF, the increasing crystallinity of scorodite and the amorphous character of the coexisting FO phase increases the stability field of scorodite relative to that of the FO to near-neutral pH values. The kinetic inability of amorphous FO to crystallize probably results from the presence of high concentrations of sulfate and arsenate. ? 2006 Elsevier Inc. All rights reserved.
Keywords: AMORPHOUS MEDIUM; CRYSTALLINITY; GEOCHEMICAL METHOD; MINE; MINERAL PROPERTY; SOLUBILITY; TAILINGS